PENGEMBANGAN KURIKULUM MULTIKULTURAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI INDONESIA - Huda, Ali Anhar Syi'bul; Firdaus, Endis; Nurhuda, Abid; Lathif, Nur Muhammad (Universitas Nahdlatul Ulama Surakarta, 2024)
In carrying out educational activities, it is necessary to have several supports, including curriculum, media, methods, facilities and infrastructure, and monitoring. As for this article, the main highlight is the development of a multicultural-based curriculum in learning Islamic religious education (PAI) in Indonesia. The multicultural approach is very important and crucial in the midst of the diversity of Indonesian society from Sabang to Merauke, so it is suitable if the approach is also applied to the field of education. The purpose of the study of this article is to find out what is meant by multicultural curriculum, the stages in implementing multicultural curriculum, multicultural curriculum in PAI learning in Indonesia, and the challenges of implementing multicultural curriculum. The research design uses a qualitative approach with the specification of the method, namely research reports, data analysis techniques using descriptive analytics, and primary data collection through books, journals, proceedings, papers, and reports while secondary data is taken from valid internet sources as well as documentation. The results revealed that multicultural curriculum development in PAI learning is implemented through programs, curriculum, administrative documents, syllabus, rpp, methods, and evaluation. The development of a multicultural curriculum has also been able to form tolerant learners, honing their skills in solving problems mainly related to the existing cultural diversity. In the future, it is hoped that the multicultural curriculum will be maximized as a solution in the midst of the diversity of Indonesian society, especially in PAI learning.